Effect of aortic cross-clamp time on late survival after isolated aortic valve replacement - Swinkels, Ben M; ten Berg, Jurriën M; Kelder, Johannes C; Vermeulen, Freddy E; Van Boven, Wim Jan; de Mol, Bas A (Interactive cardiovascular and thoracic surgery, 2021)
Abstract OBJECTIVES Longer aortic cross-clamp (ACC) time is associated with decreased early survival after cardiac surgery. Because maximum follow-up in previous studies on this subject is confined to 28 months, it is unknown whether this adverse effect is sustained far beyond this term. We aimed to determine whether longer ACC time was independently associated with decreased late survival after isolated aortic valve replacement in patients with severe aortic stenosis during 25 years of follow-up. METHODS In this retrospective cohort study, multivariable analysis was performed to identify possible independent predictors of decreased late survival, including ACC and cardiopulmonary bypass (CPB) time, in a cohort of 456 consecutive patients with severe aortic stenosis, who had undergone isolated aortic valve replacement between 1990 and 1993. RESULTS Mean follow-up was 25.3 ± 2.7 years. Median (interquartile range) and mean ACC times were normal: 63.0 (20.0) and 64.2 ± 16.1 min, respectively. Age, operative risk scores and New York Heart Association class were similar in patients with ACC time above, versus those with ACC time below the median. Longer ACC time was independently associated with decreased late survival: hazards ratio (HR) 1.01 per minute increase of ACC time (95% confidence interval [CI] 1.00–1.02; P = 0.012). Longer CPB time was not associated with decreased late survival (HR 1.00 per minute increase of CPB time [95% CI 1.00–1.00; P = 0.30]). CONCLUSIONS Longer ACC time, although still within normal limits, was independently associated with decreased late survival after isolated aortic valve replacement in patients with severe aortic stenosis. Previous studies have shown that longer aortic cross-clamp (ACC) time is independently associated with decreased early survival after cardiac surgery [1].